Evaluation of CdSe/CdS-PEG-FA quantum dots: Distribution and observable-adverse-effect-level in mice after intravenous injection - Haque, M.M.; Im, H.-Y.; Seo, J.-E.; Hasan, M.; Sailendra Nath Sarma; Woo, K.; Kwon, O.-S. (2012)
Tissue distribution and observable-adverse-effect-level of cadmium selenide/cadmium sulfide (CdSe/CdS) quantum dots (QDs) were investigated to get important information of this QDs. Female BALB/c mice were treated with single intravenous (IV) injection of polyethylene glycol-folic acid-coated QDs (CdSe/CdS-PEG-FA) at different concentrations (0, 270, and 540 pmol/20 g of mice body weight), and the subsequent toxicological effect-levels were examined for 24 h. The health and apparent behaviors of the animals were normal throughout the study. The distribution of the QDs was observed in the spleen, liver, lung and kidneys, but not in the brain and heart tissues. The spleen and liver possess the highest amount of the QDs followed by the lung while the kidneys possess the few. There were no changes in the organ weight index, total protein concentration, LDH activity, and specific NADPH oxidase activity in any tested organ indicating no toxic effects of the QDs in our study. Additionally, histopathological examination did not show any cellular/tissue structural damages. Overall, single IV administration of CdSe/CdS-PEG-FA QDs to BALB/c mice allows immediate systematic availability, and showed different tissue distribution without any obvious toxic effects at our experimental design. ？ 2012 The Korean Society of Pharmaceutical Sciences and Technology.